A critical review and re-assessment of theories of smallholder decision-making: a case of conservation agriculture households, Zambia. Issue 3 (23rd May 2013) - Umar, Bridget Bwalya
Abstract: Different theories have been posited that try to explain the decision-making process of smallholders especially regarding the adoption of new technologies or new agricultural techniques. The objective of this paper is to review and re-assess the dominant household production theories to explain the decision making of smallholders practicing conservation agriculture (CA) in the southern, eastern, and central provinces of Zambia. It also discusses the potential role of CA toward economic development. It finds that the CA smallholders studied did not aim to maximize profits but tried to secure household consumption from their own production before any other considerations in risky and uncertain environments. Their response to economic incentives was contingent on minimizing risks associated with securing a minimum level of livelihood and investing into local forms of insurance. This paper concludes that the ability for CA to contribute to rural livelihoods and economic development would depend on how adequately the factors that hinder smallholder agricultural development in general are addressed.